Condensed tannins in tropical legume fodder trees; characterisation, and interactions with rumen microbes, feed, and endogenous proteins. - Kariuki, I.W. (University of Queensland, 2004)
An extensive review of the literature on the chemistry and biological activity of condensed tannins (Chapter 1 and 2) revealed some significant gaps in knowledge of these processes, and the following experimental program was designed to investigate some specific aspects of the chemical and biological effects of condensed tannins (CT) in animals fed CT-containing diets.